Electrochemically initiated formation of sulfonyl radicals: synthesis of oxindoles via difunctionalization of acrylamides mediated by bromide ion. Issue 23 (20th September 2016) - Jiang, Yang-Ye; Liang, Sen; Zeng, Cheng-Chu; Hu, Li-Ming; Sun, Bao-Guo
Abstract : Electrochemical access to oxindoles has been developed using NH4 Br as a mediator in an undivided cell. Abstract : An efficient electrochemical approach for the synthesis of oxindoles has been developed from electrolysis of a mixture of sodium sulfinate and acrylamide. The chemistry avoids the utilization of additional conducting salt and proceeds in a simple undivided cell employing a catalytic amount of NH4 Br (10 mmol%) as a redox catalyst. The protocol is practical, as proved by the one-pot, two-step procedure and scaled-up experiments. Mechanistic studies reveal that the electrochemical approach involves the formation of sulfonyl radicals via homolytic cleavage of in situ generated sulfonyl bromide.